Information Search dalam Pembelajaran terhadap Literasi Sains: Studi pada Mahasiswa Calon Guru - Nur Wakhidah*; Nuril Fitri Amaliyah; Nailil Inayah; Erman Erman (Jurnal Pendidikan Sains Indonesia, 2022)
Students in the millennial era are very dependent on the internet so that all activities cannot be separated from handphones. This condition can be used in learning, to assign students to look for information on the internet in doing assignments, compiling papers, and during presentation discussions. This study aims to determine the difference in scientific literacy before and after learning with information search on biology topics. This research with one group pretest-posttest design involving 26 students of UIN Sunan Ampel. Data collection techniques with tests. Tests are given before and after learning with information search. Data analysis was done by t-test, ANOVA, and regression. The calculation of the n-gain value was also carried out to determine the increase in scientific literacy.  T-test shows there are differences in students' scientific literacy before and after learning with information search. Although different, the increase is still low because of the n-gain value of 0.28 (low category). Based on the results of the ANOVA test, it can be seen that are differences in the dimensions of content, process, and process. Tukey test obtained the highest average on the content dimension. Information search has the best effect on content learning so that the content dimension contributes the most to scientific literacy